Flashcard Learning Media Improves Mathematics Outcomes in Elementary Students: Media Pembelajaran Flashcard Meningkatkan Hasil Belajar Matematika Siswa Sekolah Dasar - Febrianti, Febrianti; Zulnuraini, Zulnuraini; Khairunnisa, Khairunnisa; Azizah, Azizah; Purbarani, Dyah Aini (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Mathematics learning in elementary schools often involves abstract concepts that are difficult for students to understand, requiring appropriate instructional media to support conceptual clarity. Specific Background: Fourth-grade students at SD Inpres Perumnas demonstrated low mathematics learning outcomes due to conventional teaching methods and limited use of interactive media. Knowledge Gap: Previous studies have not specifically examined the use of flashcard learning media in the context of Grade IV students at SD Inpres Perumnas, particularly for semi-abstract mathematical content such as geometric shapes. Aims: This study aims to determine the role of flashcard learning media in improving students’ mathematics learning outcomes. Results: Using a quantitative quasi-experimental design with a one-group pretest–posttest approach involving 28 students, the findings show a substantial increase in mean scores from 38.21 to 86.78, supported by paired sample t-test results with significance <0.001, indicating a statistically significant improvement. Novelty: The study provides empirical evidence within a specific local context and grade level, focusing on visual-concrete learning media for more complex elementary mathematics topics. Implications: Flashcard media can serve as an alternative instructional strategy to facilitate visual understanding, increase student engagement, and support improved learning outcomes in elementary mathematics education. Highlights• Significant score increase observed between pretest and posttest results• Visual-concrete media supports clearer understanding of geometric concepts• Student engagement during learning activities becomes more active and participatory KeywordsFlashcard Learning Media; Mathematics Learning Outcomes; Elementary Education; Visual Learning; Quasi Experimental Design